TRADISI SASI PERSPEKTIF EKOLOGI MANUSIA PADA MASYARAKAT DESA FRITU KECAMATAN WEDA UTARA KABUPATEN HALMAHERA TENGAH - Mahmud, Mujais; Matheosz, Jenny Nelly; Deeng, Djefry (HOLISTIK, Journal Of Social and Culture, 2021)
Traditional people in general are very familiar with the surrounding environment. The nature of humans as socio-cultural beings is understood ecologically as one of the interrelated environments. The view of indigenous peoples regarding humans as an integral part of nature, as well as responsible behavior, full of respect and care for the survival of life in the universe. Local wisdom as a traditional knowledge of the preservation of nature and the environment is seen as something very valuable and rich in benefits in human life.Sasi tradition is one form of customary ceremony carried out by the community that aims to limit and prohibit the taking, utilizing, and use of an item or plant that is in Sasi within a certain time, which must be obeyed and obeyed by the community collectively. The implementation of Sasi aims to maintain the quality and quantity of production as a whole. Since long ago Sasi in Fritu Village aims to protect garden products such as coconuts and marine products. Sasi carried out in Fritu Village is sea Sasi, and land sasi especially for coconut plants. The implementation of Sasi in Fritu Village was led by a village head and used to be customary but after the entry of Religion, it was switched to Sasi carried out by the Church.Keywords: local wisdom, environmental preservation, human ecology